Pengolahan Ikan Asin dalam Meningkatkan Ekonomi Masyarakat Desa Sungai Itik Perspektif Ekonomi Islam - Nurhayatul Hasanah; Haeran Haeran; Triyana Wulandari; Siti Fatimah; Ahmad Hidayat (Journal of Innovative and Creativity, 2025)
This study aims to determine the potential of salted fish processing to improve the economy of the Sungai Itik Village community and examine this activity from an Islamic economic perspective. Sungai Itik Village is a coastal village in East Tanjung Jabung Regency, where the majority of the population relies on marine resources for their livelihood, including traditional salted fish processing. The method used in this study is a descriptive qualitative approach, with data collection techniques through observation, interviews, and documentation. The informants included salted fish processing businesses, collectors, community leaders, religious leaders, and the village head. The research results show that salted fish processing has a significant contribution to improving the community's economy. This business is able to create jobs, increase family income, and reduce dependence on formal employment. Furthermore, this business is self-sufficient, sustainable, and has a multiplier economic impact on the surrounding community. From an Islamic economic perspective, salted fish processing reflects Sharia-compliant muamalah principles, such as honesty, mutual assistance (ta'awun), and blessings in business. This activity avoids the practices of usury, gharar, and fraud, and supports the Sharia goals of safeguarding wealth (hifzh al-mal) and creating the welfare of the community (maslahah).